2016
DOI: 10.1155/2016/6087896
|View full text |Cite
|
Sign up to set email alerts
|

Motor Cortex Plasticity during Unilateral Finger Movement with Mirror Visual Feedback

Abstract: Plasticity is one of the most important physiological mechanisms underlying motor recovery from brain lesions. Rehabilitation methods, such as mirror visual feedback therapy, which are based on multisensory integration of motor, cognitive, and perceptual processes, are considered effective methods to induce cortical reorganization. The present study investigated 3 different types of visual feedback (direct, mirrored, and blocked visual feedback: DVF, MVF, and BVF, resp.) on M1 cortex excitability and intracort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
(53 reference statements)
2
23
1
Order By: Relevance
“…First, based on the instantaneous neural adaptations measured using electroneurological methods, ageing predominantly influences motor improvement of the untrained limb during long-term exercise in a steady and effective manner. Although MTr significantly activated the neurological pathways compared with normal training in previous studies,46–49 more time might be needed for the neural adaptations to support functional changes. Second, the included study did not use a continuous endurance training regimen to elicit better performance by memory consolidation compared with simple tasks in older adults 50 51.…”
Section: Discussionmentioning
confidence: 79%
“…First, based on the instantaneous neural adaptations measured using electroneurological methods, ageing predominantly influences motor improvement of the untrained limb during long-term exercise in a steady and effective manner. Although MTr significantly activated the neurological pathways compared with normal training in previous studies,46–49 more time might be needed for the neural adaptations to support functional changes. Second, the included study did not use a continuous endurance training regimen to elicit better performance by memory consolidation compared with simple tasks in older adults 50 51.…”
Section: Discussionmentioning
confidence: 79%
“…Recent results indicate that a combination of motor training with mirrored visual feedback (MVF) therapy can induce significant neuroplasticity changes through multisensory integration. The findings of this finger movement therapy lend support to the application of finger calligraphy writing for inducing cortex plasticity in the course of treatment (Kumru et al, 2016). We have made initial attempts to develop finger writing as a new mode for calligraphy therapy.…”
Section: Finger Writing: the New Instrumentmentioning
confidence: 56%
“…Our results indicate that visual feedback of movement affects corticospinal excitability in a manner similar to actual movement. In a study using paired-pulse TMS, Kumru et al [8] reported that visual feedback plays an important role in modulating motor cortex excitability. Our results indicate that dynamic visual feedback elicits greater changes in corticospinal excitability than static visual feedback (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Visual information from motor imagery reduced MEP latency or facilitated corticospinal excitability [6,7]. In experiments using a mirror, Kumru et al [8] reported that visual feedback played an important role in modulating motor cortex excitability. Since the subjects in those experiments moved their own nger, it is possible that both somatosensory information and motor commands were associated with changes in corticospinal excitability of the target muscle.…”
Section: Introductionmentioning
confidence: 99%